Green surfactant of marine origin exerting a cytotoxic effect on cancer cell lines. Issue 65 (16th July 2015) - Das, Palashpriya; Sarkar, Siddik; Mandal, Mahitosh; Sen, Ramkrishna
<x xml:space="preserve">Abstract</x> The present work reveals the efficacy of a marine antimicrobial lipopeptide biosurfactant in blocking proliferation of breast cancer and colon cancer cell lines, without displaying any significant antioxidant activity.